"LARGE HADRON COLLIDER" WITH DIFFERENT METHODS - Bobokulovna, Mardanova Feruza (Confrencea, 2022)
At first glance, Fans of spectacular spectacles, like a cloud mushroom over a nuclear test site or the bluish glow of Vavilov — Cherenkov in a reactor, have nothing to do here. All the most interesting things happen in tightly sealed pipes